2018
DOI: 10.3386/w24792
|View full text |Cite
|
Sign up to set email alerts
|

Banks, Insider Connections, and Industrialization in New England: Evidence from the Panic of 1873

Abstract: for research assistance. The author declares that he has no relevant or material financial interests that relate to the research described in this paper. The views expressed herein are those of the author and do not necessarily reflect the views of the National Bureau of Economic Research. NBER working papers are circulated for discussion and comment purposes. They have not been peer-reviewed or been subject to the review by the NBER Board of Directors that accompanies official NBER publications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 41 publications
(50 reference statements)
2
6
0
Order By: Relevance
“…Earnings bottomed out in 1878, the last year of the Long Depression, and started to recover thereafter. This pattern is consistent with the timing of the crisis documented by Hilt (2015) based on firm-level data.…”
Section: B2 Crisis Period (1873 To 1880)supporting
confidence: 86%
See 2 more Smart Citations
“…Earnings bottomed out in 1878, the last year of the Long Depression, and started to recover thereafter. This pattern is consistent with the timing of the crisis documented by Hilt (2015) based on firm-level data.…”
Section: B2 Crisis Period (1873 To 1880)supporting
confidence: 86%
“…Lamoreaux (1994) refers to this as "insider lending." Hilt (2015) confirms that this state of affairs persisted into the 1870s.…”
Section: E Bank Governancesupporting
confidence: 52%
See 1 more Smart Citation
“…The Economist, in its May 1901 issue, reported that Russian '(b)anks generally have been in 5 of 34 difficulties from having sunk too much money in loans to factories as working capital, which, though paying a high rate of interest, could not be readily called in when money was urgently required' (p. 667). As is often the case, it is companies with better financial backing that weather a crisis, not necessarily the most efficient ones (Franklin et al, 2015;Hilt, 2017). As a result, banks' response to the crisis created corporate winners and losers by propping up large companies whilst limiting credit to smaller firms.…”
Section: << Insert Figure 1a-c Here >>mentioning
confidence: 99%
“…The example of Elijah C. Drew illustrates the mechanism we have in mind. 30 In 1872, amounted to more than 10% of paid-in capital: "I fail to be convinced that they are bona fide bills of exchange drawn against existing values of commercial or business paper actually owned by the person negotiating the same." Later, it turned out that these loans, rather than safe commercial paper, were backed with speculative real estate investments in Houston, Texas.…”
Section: Examplesmentioning
confidence: 99%